Hard to jump: host shifts appear unlikely in a T4-like phage evolved in the lab - Ning, Yu; González-Tortuero, Enrique; Wagemans, Jeroen; Arias-Sánchez, Flor I. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBacteriophage therapy is emerging as a promising alternative to antibiotics, particularly in the face of rising antimicrobial resistance. However, concerns remain regarding host shifts, where therapeutic phages could evolve to infect and harm beneficial commensal bacteria. Understanding how frequently host shifts occur and what evolutionary constraints shape them is critical to assessing the safety of phage therapy.MethodsWe investigated the evolutionary potential for host shifts using Escherichia coli-infecting phage BW-1. Experimental evolution was conducted under controlled conditions that favored adaptation, using both non-permissive (unable to infect) and semi-permissive (low infectivity) bacterial strains. Virulence was assayed across hosts, and whole-genome sequencing was used to identify mutations associated with adaptation.ResultsHost shifts were found to be rare, with no significant increases in virulence observed in non-permissive hosts. In contrast, adaptation occurred in semi-permissive hosts and was linked to trade-offs, where increased virulence in one host reduced infectivity in others. Whole-genome sequencing revealed a single convergent regulatory SNP across all phages adapted to the semi-permissive host, indicating constrained evolutionary pathways during host adaptation.DiscussionOur findings suggest that phages exhibit high host specificity, which limits the risk of host shifts to commensal bacteria. Although adaptation to semi-permissive hosts is possible, it is constrained and associated with fitness trade-offs across host ranges. These results indicate that therapeutic phages are unlikely to negatively impact intestinal microbiota, supporting their potential as safe and effective alternatives to antibiotics.